2015
DOI: 10.1099/mic.0.000144
|View full text |Cite
|
Sign up to set email alerts
|

Transfer-messenger RNA and SmpB mediate bacteriostasis in Escherichia coli cells against tRNA cleavage

Abstract: RNAs, such as mRNA, rRNA and tRNA, are essential macromolecules for cell survival and maintenance. Any perturbation of these molecules, such as by degradation or mutation, can be toxic to cells and may occasionally induce cell death. Therefore, cells have mechanisms known as quality control systems to eliminate abnormal RNAs. Although tRNA is a stable molecule, the anticodon loop is quite susceptible to tRNA-targeting RNases such as colicin E5 and colicin D. However, the mechanism underlying cellular reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Even so, new classes of CDI toxins like those encoded by the maf‐ genes in Neisseria gonorrhea (Jamet et al , ) are still being discovered, suggesting CDI systems to be even more widespread than we know. Finally, other classes of bacteriostatic toxins, like some colicins (Sakai et al , ) and Type VI secretion effectors (Whitney et al , ), could also in principal contribute to inter‐bacterial induction of persister formation at high cell densities. Thus, cell‐to‐cell contact‐mediated delivery of bacterial toxins could be a common bet‐hedging mechanism used for creating population density‐dependent heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, new classes of CDI toxins like those encoded by the maf‐ genes in Neisseria gonorrhea (Jamet et al , ) are still being discovered, suggesting CDI systems to be even more widespread than we know. Finally, other classes of bacteriostatic toxins, like some colicins (Sakai et al , ) and Type VI secretion effectors (Whitney et al , ), could also in principal contribute to inter‐bacterial induction of persister formation at high cell densities. Thus, cell‐to‐cell contact‐mediated delivery of bacterial toxins could be a common bet‐hedging mechanism used for creating population density‐dependent heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, new classes of CDI toxins like those encoded by the maf-genes in Neisseria gonorrhea (Jamet et al, 2015) are still being discovered, suggesting CDI systems to be even more widespread than we know. Finally, other classes of bacteriostatic toxins, like some colicins (Sakai et al, 2015) and Type VI secretion effectors (Whitney et al,…”
Section: Discussionmentioning
confidence: 99%
“…Further incubation, however, results in the loss of colony-forming activity, indicating that the bacteriostasis is transiently maintained for several hours. 66) This resembles the "point of no return" observed in the programmed cell death mediated by the mazEF module, one of the most studied TA systems. 67) Alternatively, the challenged cells then enter a specific phase, such as a viable but nonculturable (VBNC) state, 68) where the cells are alive but exhibit impaired colony-forming activity.…”
Section: Insight Into Trna Cleavage: Possible Roles In Growth Regmentioning
confidence: 62%
“…We found that sensitive cells were not immediately killed, but were driven into a bacteriostatic state for several hours with susceptible tRNAs almost completely cleaved. 66) This phenomenon is not limited to ts colicin D; cells challenged by wild-type colicins E5 or D maintained high viability for as long as five hours, based on LIVE/DEAD staining results. Further incubation, however, results in the loss of colony-forming activity, indicating that the bacteriostasis is transiently maintained for several hours.…”
Section: Insight Into Trna Cleavage: Possible Roles In Growth Regmentioning
confidence: 98%
See 1 more Smart Citation